2019
DOI: 10.1186/s12883-019-1253-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing early enteral nutrition in severe stroke (OPENS): protocol for a multicentre randomized controlled trial

Abstract: BackgroundMalnutrition is one of the crucial factors associated with poor prognosis in critical ill patients, yet a significant evidence gap surrounds the management of initial enteral feeding in severe stroke. The Optimizing Early Enteral Nutrition in Severe Stroke (OPENS) trial will compare a strategy of modified full enteral nutrition (EN) (standard full EN in conjunction with prokinetic drug) and a strategy of permissive underfeeding (40 to 60% of estimated caloric requirements) with standard full EN (adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…It has been demonstrated that early enteral nutrition support applied to critically ill patients can effectively prevent their secondary injuries and circumvent the occurrence of disability and death (16). Nevertheless, there are controversies regarding the nutrition time, the nutrition program, the nutrition approaches, and the nutrition complications on how to effectively and safely give early enteral nutrition support (17).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that early enteral nutrition support applied to critically ill patients can effectively prevent their secondary injuries and circumvent the occurrence of disability and death (16). Nevertheless, there are controversies regarding the nutrition time, the nutrition program, the nutrition approaches, and the nutrition complications on how to effectively and safely give early enteral nutrition support (17).…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests enteral feeding rates within the acute stroke population are between 10% and 20% (Rowat, 2015; Martin, 2005; Yuan et al., 2019). Interestingly, this chart review found over a quarter of patients required enteral feeding during their admission.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter randomized controlled study Optimizing early enteral nutrition in severe stroke (OPENS) is being performed in China 21) . The results of that study and other similar studies must be considered in the formulation of further nutritional support strategies for the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is mandatory to consider such disease characteristics in the provision of nutritional support. However, few studies have focused on nutritional support for CVA 11,21) .…”
Section: Introductionmentioning
confidence: 99%